ANALISIS HUBUNGAN FAKTOR INDIVIDU DENGAN PERSEPSI RISIKO KARYAWAN PT X TERHADAP COVID-19 DI PROYEK LINTAS REL TERPADU - Fahzrin Perwita; Mila Tejamaya (Universitas Pahlawan, 2022)
To April 2021, COVID-19 cases in Indonesia reaches 1.668.368 with the death cases are 45.334. The increasing death cases due to COVID-19 worldwide and the presence of 14 employess exposed to COVID-19 in the project area specifically encouraged this study. This study aims to observe the relationship between individual factors and the risk perception againts COVID-19 among the employess in LRT Project PT X during April-May 2021. The results revealed that based on the individual factors, the composition of the respondents are 83,3% of male, aged 20–30 years old (56,7%), hold a bachelor degree (58,3%), have not infected with COVID-19 (88,3%), and do not have a chronic disease (100%). Overall, the risk perception of the respondents is relatively high (51,7%; n=62), and as much as 48,3% (n=58) of respondents have low risk perception against COVID-19. The result of the risk perception analysis showed that the factor of age has a significant relationship with the level of risk perception, level of knowledge, potential impact, readiness and self-efficacy, fear, severity, and voluntary of risk. The factor of gender is significantly related to readiness and self-efficacy, novelty, and severity. The education level is known to have a significant relationship with the entire variabels of risk perception. However, the factor of COVID-19 infected history is significantly related to the knowledge level, control over risk, and novelty. The health status of the respondents has a constant value because no respondent has a chronic disease so its relationship to other variables cannot be statistically made. Keywords : Age, COVID-19, Individual Factors, LRT Project, Risk Perception